Associations between adherence to MIND diet and general obesity and lipid profile: A cross-sectional study - Fateh, Hawal Lateef; Muhammad, Sarmad S.; Kamari, Negin (Frontiers in Nutrition, 2023)
Background: The term "Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND)" has recently been coined to describe a new eating pattern. Recent research is looking at how this food pattern affects chronic illnesses. Thus, this study aimed to investigate the association between the use and adherence to the MIND diet with general obesity and blood lipid profile. Methods: In this cross-sectional study, 1328 Kurdish adults between the ages of 39 and 53 had their dietary intake evaluated using a valid and reliable 168-item Food Frequency Questionnaire (FFQ). Adherence to the MIND diet was examined based on the components advised in this eating pattern. Each subject's lipid profiles and anthropometric measurements were documented. Results: The mean age and BMI in the study population were 46.16 ± 7.87 y and 27.19± 4.60 kg/m2, respectively. The chances of having increased serum Triglycerides (TG) were 42% lower in those in the third tertile of the MIND diet score compared to those in the first tertile (ORs: 0.58; 95% CI 0.38-0.95; P = 0.001). In the crude model and after adjusting for confounders, lowering high-density lipoprotein cholesterol (HDL-C) (ORs: 0.72; 95% CI 0.55-1.15; P = 0.001). Conclusions: We found that greater adherence to the MIND diet was associated with the decrease odds of general obesity and lipid profile. Further study is essential owing to the relevance of chronic diseases like MetS and obesity in health status.